H, Hubungan Hubungan Persepsi, Sumber Informasi Dan Sikap Ibu Hamil Terhadap Pemeriksaan Triple Eliminasi Di Puskesmas Margasari - Sari, Ria Puspita Eka; Suhartati, Susanti; Yuliantie, Putri; Lestari, Yayuk Puji (An Idea Health Journal, 2024)
The triple elimination program is the government's effort to break the chain of transmission of infection from mother to child. The initial risk location of HIV, syphilis and hepatitis B infections can be resolved through blood tests at least once during pregnancy. The achievement of pregnant women who underwent triple elimination check-ups at the Margasari Community Health Center in January-September 2023 was 58.5%. to determine the relationship between perceptions, sources of information and attitudes of pregnant women towards triple elimination examinations at the Margasari Community Health Center. The type of research used is an analytical survey using quantitative data with a cross sectional approach. Samples were taken using accidental sampling technique as many as 40 respondents. Data collection was carried out using a questionnaire. Bivariate data analysis using chi-square. 21 pregnant women who had undergone triple elimination examination (52.5%), 21 pregnant women with positive perceptions (52.5%), 22 pregnant women with bad information sources (55%), pregnant women with positive attitude 34 people (85%). The results of the analysis show that there is a relationship between perception (p value = 0.000), source of information (p value = 0.000) and attitude (p value = 0.007) towards the triple elimination examination. There is a relationship between perceptions, sources of information and attitudes of pregnant women towards triple elimination examinations at the Margasari Community Health Center.